THE INCENTIVE EFFECT OF FRINGE BENEFITS IN ENCOURAGING THE POPULATION TO LEAD A HEALTHY LIFESTYLE - Molnár, Anikó; Müller, Anetta (Acta Carolus Robertus, 2021)
The aim of our research was to examine the incentive effect of fringe benefits on a healthy lifestyle. To this end, we examined both the employers’ and the employees’ side. When analyzing the employer segment, companies (N = 41) were asked about the importance of a healthy workforce and the initiatives they use to encourage their employees to lead a more active lifestyle. In the employee (N=133) segment, we asked questions about their lifestyle, their sporting habits, the utilization of the examined fringe benefits (SZÉP Card, All You Can Move SportPass), and among the respondents who did not have a card, if there would be an initiative from the employer’s side would they use it. The results highlighted that health-conscious behaviour is present on both sides, however, companies show less engagement. Moreover, data showed that by using the cards employees indeed participate in more sporting activities, and those who do not have it have shown a high willingness to use it. In addition, employees generally believe that such benefits improve the image of employers as well.
Keywords: well-being; incentives; employees well-being; healthy lifestyle